Medición del grosor de materiales usando microondas - Flórez Torres, Ramón G. (Ingeniería, 2001)
The monitoring and measurement of thin materials in movement has to be done in a continuous way, there must be un physical contact with the material and it should not suffer any alterations. Thus, because of the reason previously exposed, the use of a micrometer should be avoided. The techniques of width measurement using radiosotops comprohend the mentioned caractheristic.